Pendampingan Santri Madin dalam Belajar Bahasa Arab di Ponpes As-Sunniyyah Jember - Asni Furoidah; Wikke Inggawati Siska (An-Nuqthah, 2022)
This mentoring activity is carried out for Madrasah Diniyah (Madin) students who are studying Arabic at the As-Sunniyyah Islamic Boarding School Kencong Jember. The orientation of Madin santri mentoring is directed at improving the quality of speaking skills (maharah al-kalam) and understanding Arabic for students. The purpose of this service research was to assist Madrasah Diniyah students in the communicative process of learning Arabic. This service research used the community development method. The results of the mentoring activities for Madrasah Diniyah students showed the effectiveness of communicative Arabic learning for students, increase motivation to learn Arabic and foster an active and creative spirit of As-Sunniyyah As-Sunniyyah Madrasah students in Jember. Mentoring Madin students can hone their skills in Arabic.